Linguistic policy in the camps of Sahrawi refugees - Martos, Isabel Molina (2014)
In this paper, we refer to the situation of the Spanish Language among the Sahrawi people, a heritage of their Colonial past. We’re interested in examining the policies that have been implemented by the Polisario Front since the 70’s, geared towards the return of their territory, which has been occupied by Morocco since 1975, and towards the recognition of their national state, the Saharan Arab Democratic Republic. Central to the creation of the Sahrawi national state is the recognition of a cultural tradition clearly different to that of surrounding countries. We concentrate on the function the Sahrawi people attribute to the Spanish language, as part of that cultural tradition, in the configuration of a national state with full international recognition, independent of Morocco and its Francophone heritage.